PEMILIHAN TEMPAT KOS MENGGUNAKAN ALGORITMA SIMPLE ADDITIVE WEIGHTING DAN ALGORITMA FUZZY MULTI-ATTRIBUTE DECISION MAKING - Megah Sari, Dian; Al Farisiy, Salman; arifin, Nurhikma (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
Determination of where to live in a newly recognized area is influenced by many factors, including distance, price, facilities, room size, vehicle, house design and vehicle costs. This journal determines the criteria used in choosing a place to live. These criteria are analyzed using simple addtive weighting (saw) algorithm and fuzzy multi-attribute decision making algorithm. The results of the analysis obtained are in the form of location criteria to determine the most suitable boarding place because the presence of boarding houses around public facilities is expected for newcomers to a new area. With the advancement of information technology, it can answer the need for finding a boarding house, and will be of great help both from the side of the owner and tenant. And not only that, with this internet technology, prospective tenants can also choose a boarding house according to their wishes. Planning a system that can assist in determining temporary housing is needed by tenants in finding housing that fits the desired criteria. By making an SPK (Decision Support System) Selection of Boarding House is expected to help solve the problem of alternative housing. Therefore we need a website that makes a decision support system to determine temporary